Researching mega-events under regulatory capitalism - Nichols, G.; Benson, A.; Holmes, Kirsten (Cognizant Communication Corporation, 2018)
A significant legacy of the 2012 Olympic Games was to demonstrate how such an event could be delivered within the governance structure of "regulatory capitalism." The delivery of the London 2012 Games was contracted to a private company, the London Organizing Committee of the Olympic Games and Paralympic Games (LOCOG). LOCOG subcontracted packages of work, including Games research, which was conducted by a market research company as "sponsorship" in kind. Through an autoethnographic account of researching volunteers at these Games, working with the market research company, it is shown how: public accountability was reduced by the selective availability of research results; the access to research became a marketable resource; and research ethics of the private company were inconsistent with those required within a University. Therefore, the delivery of the Games through regulatory capitalism reinforced the unequal power relationships between the different event stakeholders. This leads to a discussion of implications for researching mega-events and the relationship between academic research and commercial researchers. These include the need for researchers to pay for access and to protect their intellectual property.